Direct role for the Drosophila GIGYF protein in 4EHP-mediated mRNA repression. Issue 13 (22nd May 2019) - Ruscica, Vincenzo; Bawankar, Praveen; Peter, Daniel; Helms, Sigrun; Igreja, Cátia; Izaurralde, Elisa
Abstract: The eIF4E-homologous protein (4EHP) is a translational repressor that competes with eIF4E for binding to the 5′-cap structure of specific mRNAs, to which it is recruited by protein factors such as the GRB10-interacting GYF (glycine-tyrosine-phenylalanine domain) proteins (GIGYF). Several experimental evidences suggest that GIGYF proteins are not merely facilitating 4EHP recruitment to transcripts but are actually required for the repressor activity of the complex. However, the underlying molecular mechanism is unknown. Here, we investigated the role of the uncharacterized Drosophila melanogaster ( Dm ) GIGYF protein in post-transcriptional mRNA regulation. We show that, when in complex with 4EHP, Dm GIGYF not only elicits translational repression but also promotes target mRNA decay via the recruitment of additional effector proteins. We identified the RNA helicase Me31B/DDX6, the decapping activator HPat and the CCR4–NOT deadenylase complex as binding partners of GIGYF proteins. Recruitment of Me31B and HPat via discrete binding motifs conserved among metazoan GIGYF proteins is required for downregulation of mRNA expression by the 4EHP–GIGYF complex. Our findings are consistent with a model in which GIGYF proteins additionally recruit decapping and deadenylation complexes to 4EHP-containing RNPs to induce translational repression and degradation of mRNA targets.